2019
DOI: 10.1096/fj.201900830r
|View full text |Cite
|
Sign up to set email alerts
|

NEAT1 is overexpressed in Parkinson's disease substantia nigra and confers drug‐inducible neuroprotection from oxidative stress

Abstract: Recent reports attribute numerous regulatory functions to the nuclear paraspeckle‐forming long non‐coding RNA, nuclear enriched assembly transcript 1 (NEAT1), but the implications of its involvement in Parkinson's disease (PD) remain controversial. To address this issue, we assessed NEAT1 expression levels and cell type patterns in the substantia nigra (SN) from 53 donors with and without PD, as well as in interference tissue culture tests followed by multiple in‐house and web‐available models of PD. PCR quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 65 publications
2
62
0
Order By: Relevance
“…Moreover, the inflammation regulator NFkB1 was only increased under SARS-CoV-2 infection ( Figure 2B ). Both DANCR and the sepsis-related neuroprotective lncRNA NEAT1, which initiates and maintains the membrane-less organelle of nuclear paraspeckles ( 30 , 33 , 39 ), were suppressed in SARS-CoV-2 infected cells ( Figure 2C ) (see corresponding Resource in Supplementary Table 1 for the full list of lncRNAs changed in NHBE and A549 cells infected with SARS-CoV-2, in NHBE cells infected with pandemic H1N1, and in lung inflammatory samples). Together, these observations indicated that inter-related changes in DANCR, NEAT1, and NFkB1 might play specific regulatory roles in the natural history of SARS-CoV-2 infection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the inflammation regulator NFkB1 was only increased under SARS-CoV-2 infection ( Figure 2B ). Both DANCR and the sepsis-related neuroprotective lncRNA NEAT1, which initiates and maintains the membrane-less organelle of nuclear paraspeckles ( 30 , 33 , 39 ), were suppressed in SARS-CoV-2 infected cells ( Figure 2C ) (see corresponding Resource in Supplementary Table 1 for the full list of lncRNAs changed in NHBE and A549 cells infected with SARS-CoV-2, in NHBE cells infected with pandemic H1N1, and in lung inflammatory samples). Together, these observations indicated that inter-related changes in DANCR, NEAT1, and NFkB1 might play specific regulatory roles in the natural history of SARS-CoV-2 infection.…”
Section: Resultsmentioning
confidence: 99%
“…Correspondingly, we identified DANCR as prominently reduced under SARS-CoV-2 infection, together with the lncRNA NEAT1 which controls RNA-regulating processes via forming the non-membranous organelle of the nuclear paraspeckles. Of note, NEAT1 interacts with inflammatory pathways, leading to transcriptional activation of IL-8 ( 110 ) and protecting human-originated neuronal cells under oxidative stress in a manner mediated by lipid lowering medications (such as statins) ( 33 ). NEAT1 is further implicated in inflammation by its association with controllers of inflammasome-associated proteins, and by its assembly with other molecular elements into an immune-controlling ribonuclear complex ( 111 , 112 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NEAT1 has been most frequently studied in various cancer as an oncogene, including cervical cancer [22], colon cancer [23] as well as glioma [24] by regulating cell migration, proliferation along with drug resistance. Additionally, NEAT1 was upregulated in Parkinson's disease and conferred drug-inducible neuroprotection against oxidative stress [25]. Also, NEAT1 expression was enhanced in patients suffered from acute ischemic stroke versus controls, which could predict unsatisfactory recurrence-free survival [26].…”
Section: Discussionmentioning
confidence: 99%